PENINGKATAN MUTU PENDIDIKAN DENGAN PENERAPAN MANAJEMEN BERBASIS SEKOLAH (Studi di SMPS Katolik Mater Inviolata Larantuka-Flores) - Yustina; Hotner Tampubolon (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2018)
The purpose of this research to describe the application of quality improvement strategies with MBS in Catholic Mater Inviolata Larantuka Junior High School. The subject of the research,the principal,the teachers,the school committee,and the school community. The research method is descriptive qualitative. Data collection is done with the interview techniques, observation and study of the documentation. The results of the research are that: (1) Application of strategy: Continuous program planning, through programming each year of lessons; improvement of academic and non academic quality by streamlining learning time, improvement program and enrichment; empowering the professionalism of teachers and staff through professional development training;empowering potential learners through additional learning hours, learning assistance; cooperate with parents through regular meetings at the beginning, of the middle and end of the semester. (2) The role of the principal as: (a) Educator: foster, train teachers through various trainings.(b) Managers: planning and developing school programs. (c) Administrator: orderly administration of each task field. (d) Supervisor: supervise the performance of teachers and staff. (e) Leader: a democratic leadership. (f) Innovators: The new innovations; IT training program. (g) Motivators: motivate teachers, staff, students to develop potential. (3) The role of teachers: as implementing PAKEM-based teaching and learning activities. (4) The role of the school committee: realized in giving consideration to the host and the implementation of education policy, following up the aspirations of the community. (5) The role of the community through participation in program implementation, providing financial assistance, and personnel.